Euglycemic ketoacidosis complicating empagliflozin therapy in a Bangladeshi type 2 diabetic lady - Laboni, Rezwana; Afsana, Faria; Hossain, Kazi Nazmul; Binte Rouf, Rushda Sharmin; Amin, Mohammod Feroz; Ashrafuzzaman, SM; Pathan, Md Faruque (BIRDEM Medical Journal, 2021)
Diabetic ketoacidosis (DKA) is an acute complication of diabetes mellitus, which may occurin both type 1 and type 2 diabetic patients. It is characterized by hyperglycaemia [blood glucose levels > 250 mg/dL (13.8 mmol/ L)], metabolic acidosis (pH <7.3 or serum bicarbonate <15 mmol/L) with an increased anion gap and the presence of ketone bodies in blood or urine. A subgroup of patients may present without signs of hyperglycemia, rather present with euglycemia, posing a diagnostic challenge due to the absence of the cardinal findings of the pathophysiology in DKA. Here, we report a case of euglycemic ketoacidosis complicating a 50-year-old Bangladeshi diabetic lady receiving empagliflozin treatment. BIRDEM Med J 2021; 11(3): 243-245